Keefektifan Cognitive Behavior Theraphy untuk Mengurangi Perilaku Phubbing pada Peserta Didik SMP - lintang Rum Hapsari; Ulya Makhmudah; Ma'rifatin Indah Kholili (Universitas Sebelas Maret, 2022)
Abstract: This study aimed to test the effectiveness of cognitive behavior therapy (CBT) in reducing phubbing behavior in junior high school students. This study uses an experimental method with a single case experimental design, the A-B design. Two male students in class VIII were the subjects of this study—data collection techniques using interview and observation guidelines. Data analysis used a split middle technique, and clinical analysis used a subjective evaluation method. The results of data analysis using the split middle technique, both research subjects, namely GFP and MIZ, experienced a decrease or change in behavior in the intervention phase compared to the baseline phase. The results of the split middle technique data show that the GFP subject has a slope of 0.48 and a change of 1.58. At the same time, the MIZ subject has a change in slope of 0.3 and a change in the level of 1.8. In line with the results of the split middle technique, based on the results of the clinical analysis with subjective evaluation, it was explained that the phubbing behavior of the subject had decreased. It was concluded because of the efforts of the two subjects to reduce phubbing behavior. It can be concluded that cognitive restructuring techniques are effective in reducing phubbing behavior in class VIII SMP students.Abstrak: Tujuan penelitian ini adalah menguji keefektifan cognitive behavior therapy (CBT) untuk mengurangi perilaku phubbing pada peserta didik SMP. Penelitian ini menggunakan metode eksperimen dengan single case experimental design, rancangan desain A-B. Dua peserta didik laki-laki kelas VIII menjadi subjek dalam penelitian ini. Teknik pengumpulan data menggunakan pedoman wawancara dan pedoman observasi. Analisis data menggunakan split middle technique serta analisis klinis menggunakan metode evaluasi subjektif. Hasil analisis data menggunakan split middle technique kedua subjek penelitian yaitu GFP dan MIZ mengalami penurunan atau perubahan perilaku di fase intervensi dibanding fase baseline. Hasil dari data split middle technique menunjukkan subjek GFP terdapat perubahan slope 0.48 dan perubahan level 1.58. Sedangkan subjek MIZ terdapat perubahan slope 0.3 dan perubahan level 1.8. Senada dengan hasil split middle technique tersebut, berdasarkan hasil analisis klinis dengan evaluasi subjektif menjelaskan bahwa perilaku phubbing pada subjek mengalami penurunan. Hal tersebut disimpulkan karena adanya usaha dari kedua subjek untuk mengurangi perilaku phubbing. Maka dapat disimpulkan bahwa teknik cognitive restructuring efektif untuk mengurangi perilaku phubbing pada peserta didik kelas VIII SMP.